Response of Rice Varieties to Age of Seedlings and Transplanting Dates - Shah, Mishri L; Yadav, Rambaran (Nepal Agriculture Research Journal, 2011)
A field experiment was conducted at Regional Agricultural Research Station, Parwanipur in 1998/99 and 1999/00 with an aim to find out the alternate management practices to compensate the loss in the grain yield due to flood. Irrespective of the varieties and transplanting dates, age of seedlings had no effect on grain yield of rice. But transplanting dates had significant effect on grain and grain contributing characters. The yield of rice transplanted at 1 Sept was 25.6 and 37.5% less in 1998/99 and 1999/00 respectively as compared to rice grain yield of 14 July transplanting. Radha 11 registered the highest grain yield of 4086 kg ha-1 in 1999/00 and 2662 kg ha-1 in 1998/99, which was at par to the yield obtained by Sabitri at the same year. The interaction effect of the age of seedlings, transplanting dates and varieties were found significant in both the years. 25 days old seedlings transplanted on 14 July in 1999/00 of rice varieties Masuli and Radha 11, produced statistically the similar yield. Radha 11 was the best among the tested varieties. 25 days old seedlings of Masuli, Basmati, Sabitri and Radha 11 can be recommended to transplant as late as Sept 1 . Key words: Age of seedlings; Rice; Transplanting dates DOI: http://dx.doi.org/10.3126/narj.v4i0.4858 Nepal Agriculture Research Journal Vol. 4&5, 2001/2002 Page: 14-17 Uploaded date: 7 June, 2011